PERISTIWA CHINESETROUBELEN DI BATAVIA - Fokky Fuad (Jurnal Ilmiah Mimbar Demokrasi, 2013)
This study aimed to describe the genocide descriptively Chinese in Batavia that occurred in October 1740. Event known as Chinatown Chinese troubelen or commotion, is the first step of ethnic segregation in Indonesia are carried out systematically by the Trade Union of the East Indies Company (VOC). Ethnic Chinese were targeted over policy administration errors VOC in Batavia, where they need to create a tangible goal that can be used as a scapegoat of the various errors. Thus, VOCs can avoid accusations of failure of the administration